Three-dimensional CFD-solid mechanics analysis of the hydrogen internal combustion engine piston subjected to thermomechanical loads - Maher A.R. Sadiq Al-Baghdadi; Sahib Shihab Ahmed; Nabeel Abdulhadi Ghyadh (International Journal of Renewable Energy Development, 2023)
Fueling internal combustion engines with hydrogen is one of the most recommended alternative fuels today in order to combat the energy crisis, pollution problems, and climate change. Despite all the advantages of hydrogen fuel, it produces a higher combustion temperature than gasoline. In an internal combustion engine, the piston is among the numerous complex and highly loaded components. Piston surfaces are directly affected by combustion flames, making them critical components of engines. To examine the stress distribution and specify the critical fracture zones in the piston for hydrogen fuel engines, a three-dimensional CFD-solid-mechanics model of the internal combustion engine piston subjected to real thermomechanical loads was analyzed numerically to investigate the distribution of the temperature on the piston body, the interrelated thermomechanical deformations map, and the pattern of the stresses when fueling the engine with hydrogen fuel. With the aid of multiphysics COMSOL software, the CFD-solid-mechanics equations were solved with high accuracy. Despite the increase in pressure on the piston and its temperature when the engine is running on hydrogen fuel, the results show that the hydrogen fuel engine piston can withstand, safely, the thermomechanical loads. In comparison to gasoline fuel, hydrogen fuel caused a deformation of 0.34 mm, an increase of 17%. This deformation is within safe limits, with an average clearance of 0.867 mm between the cylinder liner and piston.